Tank-Mixing Pesticides without Disasters - Frederick M. Fishel (EDIS)
Tank-mixing several pesticides is a common practice in conducting pest control. Tank mixes can consist of much more than just pesticides, such as fertilizers, micronutrients, and adjuvants. However, applicators must be aware of potential problems given that there are so many potential combinations when combining these products. Manufacturers cannot possibly test for all of these combinations, so both chemical and physical incompatibility are a concern with the practice. This new 4-page document, written by Frederick M. Fishel and published by the UF/IFAS Pesticide Information Office, describes some common-sense practices to help overcome costly tank-mixing errors. https://edis.ifas.ufl.edu/pi285